Leadership Skills Series #3: Communication & Conflict Management - Jennifer Wert; Matthew Sowcik; Jera Niewoehner-Green (EDIS, 2018)
As part of the Leaders Skills Series, this publication provides Extension professionals with recommendations on how to utilize short leadership videos to address the topics of communication and conflict management. Outlined throughout the publication is a brief synopsis of each of the four different videos, a link to the videos, and recommended questions to help facilitate group discussion. After watching the videos and engaging in the discussion questions, Extension professions should have a better understanding of how to have better conservations, the impact of technology on communication, and how to handle conflict productively.